Children of problem gamblers: need for support, utilization of services and prevention policy. (20th October 2021) - Fischer, L; Klein, M
Abstract: Background: Problem gambling is an emerging European public health concern. In Germany, 25 to 33% of the approximately 229, 000 problem gamblers are also fathers or mothers of minor children. This suggests a high number of children exposed to parental gambling, who are a high-risk group for the development of addictive disorders and other psychological, somatic, and social problems. Unlike in children of parents with a substance-related addiction, the effects of parental problem gambling are under-researched and exposed children often remain underserved. In Germany, this study is the first of its kind to explore the service needs and use of services of the targeted group. Methods: Survey research with an explorative mixed-methods design was conducted in a non-representative sample (n = 67) of adolescent and adult children of problem gamblers in Germany. Data on the need for support and use of services was assessed in structured interviews and analysed using descriptive statistics and qualitative content analysis. Results: Preliminary findings in the sample (n = 67, 56, 7% male, mean age 28 years (SD = 6.966)) show a great need for support in many areas of life (e.g. family, substance use and gambling behaviour, mental health) and a low utilization of services. Exploring the need for support retrospectively, primarily (1) professional support, especially systemic / family-based support, (2) support and exchange via a trustee, (3) easily accessible services, (4) the desire for psychoeducation and transparency, (5) distancing from the gambling parent, and (6) parental willingness and ability to maintain abstinence, were considered helpful. Conclusions: Children of problem gamblers show great need of support, but low utilization of services. Further research on the practical implementation of targeted, early, easily accessible, sustainable and transgenerational prevention is a necessary measure in the delivery of care to (children from) families affected by problem gambling. Key messages: Retrospectively, children of problem gamblers express a high need of easily accessible, professional and especially family-based support and the desire for transparency and psychoeducation. Next to universal prevention, selective prevention efforts targeting children exposed to parental problem gambling are needed to reach the families at risk.